Kinematic characteristics of motor patterns in rope skipping - Luiz Henrique da Silva; Ana Maria Pellegrini (Universidade Federal de Santa Catarina, 2009)
Rope skipping seems to be an easy task to be performed. However, careful analysis of this motor skill shows how complex the execution of this task is. The objective of this study was to examine kinematic variables of jump patterns as a function of skipping frequency. Eight male university students performed a sequence of 30 rope jumps using two jump patterns (alternating support of the feet and simultaneous support of the feet) at three skipping frequencies (1.5, 1.7,1.9 Hz). Frequencies were determined with a digital metronome and the rope was turned by the student himself. Rope jumping performance was recorded with two digital cameras for 3Danalysis. Passive markers were attached to the rope and to the ankle, knee and hip joints forcollection of the following dependent variables: continuous relative phase, time interval betweenthe loss of contact of the feet with the ground and cross of the rope under the feet of the volunteer,jump height, and rope height. ANOVA showed that for the pattern with alternating support ofthe feet the jump is executed at a lower height. In addition, analysis of the time interval revealeda delay in the withdrawal of the feet for crossing the rope in the case of the jump pattern with simultaneous support of the feet.